التماسك النصي وآثاره في الدلالة القرآنية - عثمان شريف, عائشة (كلية الأدب العربي والفنون, 2024)
هذا البحث يسلط الضوء على التماسك النصي ، و أثاره في الدلالة القرآنية سورة فاطر أنموذجا على منهج لسانيات النّص وما يقدمه من جديد لتحليل النص و استكشاف آليات الاتساق النحوي و الاتساق المعجمي ، و التي أضفت بدورها على انسجام النص و أثرهما في الدّلالة القرآن ، و قد خلص البحث إلى أن سورة فاطر تخاطب العقل قبل القلب ثم الإحساس ، ممّا خلقت صلة متينة بين القارئ و الخطاب القرآني ، أما اسم السورة فهو بمثابة مفتاح وعتبة نلج منه لموضوع النص المقدس كونه يشد القارئ و يرغبه في مواصلة القراءة و التدبر، و عليه فإن التماسك النصي كان حاضرا منذ البداية This research sheds light on textual coherence, and its effect on the meaning of the Qur’an, SuratFatir, as an example of the textual linguistics approach and what it brings to the analysis of the text and exploring the mechanisms of grammatical consistency and lexical consistency, which in turn added to the coherence of the text and their impact on the meaning of the Qur’an. The research concluded that SuratFatir addresses the mind before the heart and then the feeling, which created a strong connection between the reader and the Qur’anic discourse. As for the name of the surah, it serves as a key and a threshold through which we enter the subject of the sacred text, as it attracts the reader and desires him to continue reading and contemplating, and accordingly, textual cohesion is He was present from the beginning
سورة فاطر أنموذجا
Keywords: النص ، الخطاب ، الدلالة ، التماسك النصي ، الاتساق ، الانسجام; text, discourse, connotation, textual cohesion, consistency, harmony.